Competencies and Frameworks in Interprofessional Education: A Comparative Analysis - Thistlethwaite, J.; Forman, Dawn; Matthews, L.; Rogers, G.; Steketee, C.; Yassine, T. (Lippincott William & Wilkins, 2014)
Health professionals need preparation and support to work in collaborative practice teams, a requirement brought about by an aging population and increases in chronic and complex diseases. Therefore, health professions education has seen the introduction of interprofessional education (IPE) competency frameworks to provide a common lens through which disciplines can understand, describe, and implement teambased practices. Whilst an admirable aim, often this has resulted in more confusion with the introduction of varying definitions about similar constructs, particularly in relation to what IPE actually means.The authors explore the nature of the terms competency and framework, while critically appraising the concept of competency frameworks and competency-based education. They distinguish between competencies for health professions that are profession specific, those that are generic, and those that may be achieved only through IPE. Four IPE frameworks are compared to consider their similarities and differences, which ultimately influence how IPE is implemented. They are the Interprofessional Capability Framework (United Kingdom), the National Interprofessional Competency Framework (Canada), the Core Competencies for Interprofessional Collaborative Practice (United States), and the Curtin University Interprofessional Capability Framework (Australia).The authors highlight the need for further discussion about establishing a common language, strengthening ways in which academic environments work with practice environments, and improving the assessment of interprofessional competencies and teamwork, including the development of assessment tools for collaborativepractice. They also argue that for IPE frameworks to be genuinely useful, they need to augment existing curricula by emphasizing outcomes that might be attained only through interprofessional activity.